A New Version of Quasi Biharmonic Curves with Quasi Frame - Korpinar, Talat; Oztekin, Handan (Amer Scientific Publishers, 2018)
In this study, we firstly characterize biharmonic curves and associated curvature tensor field by considering quasi frame in the ordinary space. Then, we obtain the relation of each quasi curvatures of curve in terms of biharmonic equation. Finally, we give some new conditions with constant quasi curvatures in the ordinary space.
Keywords: Quasi Frame; Fluid Flow; Biharmonic Curve; Curvatures